In Situ Stress Distribution in Cretaceous Ultra-Deep Gas Field From 1D Mechanical Earth Model and 3D Heterogeneous Geomechanical Model, Kuqa Depression, Tarim Basin, NW China - Xu, Ke; Zhang, Hui; Dong, Ruixia; Ju, Wei; Xie, Yani; Cui, Deyu; Fang, Lu; Yuan, Fang; Lai, Shujun; Liang, Jingrui; Zhang, Wei; Zhao, Bin (Frontiers in Earth Science, 2022)
The Kuqa Depression boasts rich cretaceous ultra-deep hydrocarbon resources. However, it is in complex geological conditions. At present, sufficient understandings on the in situ stress distribution and influencing factors are lacking, which restricts the process of hydrocarbon exploitation. Therefore, in this study, the Bozi gas field is selected as an example, and a 1D mechanical earth model (1D MEM) is established with the drilling data and logging data through the geomechanical method to clarify the in situ stress distribution of the wellbore. A 3D heterogeneous geomechanical model (3D HGM) is established with the constraint of 1D HEM to clarify the distribution characteristics of the 3D in situ stress field in the Bozi gas field and discuss its influencing factors. The results show that: 1) the Bozi gas field is in an extremely strong in situ stress condition with high stress values. The minimum horizontal principal stress (Sh) of the cretaceous system is 153∼180 MPa, and the maximum horizontal principal stress (SH) is nearly 200 MPa; 2) the in situ stress in the Bozi gas field has obvious vertical stratification characteristics, which can be divided into three stress sequences of “low–high–low”, with great differences in interlayer stress; 3) the in situ stress distribution of the Bozi gas field is greatly affected by the types of faulted anticline. Different types indicate different stress distribution; 4) within the influence range of overthrusts, the in situ stress in the footwall is lower than that of the hanging wall. The greater the fault offset, the greater the in situ stress difference between the hanging wall and footwall. Moreover, the lower the stress in the footwall, the higher is the degree of overthrust, and the larger is the range of footwall stress area; and 5) the means of highly deviated wells is more helpful to the Bozi gas field for hydrocarbon exploitation.